Differences between men and women in the regulation of adipose 11β‐HSD1 and in its association with adiposity and insulin resistance. Issue 11 (20th June 2013) - deSchoolmeester, J.; Palming, J.; Persson, T.; Pereira, M. J.; Wallerstedt, E.; Brown, H.; Gill, D.; Renström, F.; Lundgren, M.; Svensson, M. K.; Rees, A.; Eriksson, J. W.
<x xml:space="preserve">Abstract</x> This study explored sex differences in 11β‐hydroxysteroid dehydrogenase type 1 (11β‐HSD1) activity and gene expression in isolated adipocytes and adipose tissue (AT), obtained via subcutaneous biopsies from non‐diabetic subjects [58 M, 64 F; age 48.3 ± 15.3 years, body mass index (BMI) 27.2 ± 3.9 kg/m2]. Relationships with adiposity and insulin resistance (IR) were addressed. Males exhibited higher 11β‐HSD1 activity in adipocytes than females, but there was no such difference for AT. In both men and women, adipocyte 11β‐HSD1 activity correlated positively with BMI, waist circumference, % body fat, adipocyte size and with serum glucose, triglycerides and low‐density lipoprotein:high‐density lipoprotein (LDL:HDL) ratio. Positive correlations with insulin, HOMA‐IR and haemoglobin A1c (HbA1c) and a negative correlation with HDL‐cholesterol were significant only in males. Conversely, 11β‐HSD1 activity in AT correlated with several markers of IR and adiposity in females but not in males, but the opposite pattern was found with respect to 11β‐HSD1 mRNA expression. This study suggests that there are sex differences in 11β‐HSD1 regulation and in its associations with markers of obesity and IR.